2015
DOI: 10.4103/2231-0746.175748
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction in oral malignancy: Factors affecting morbidity of various procedures

Abstract: Aims and Objective:(1) To study the age and sex distribution of patient with oral malignancies. (2) To analyze various types of surgery performed. (3) Evaluation of reconstruction and factors affecting complications and its relation to the type of reconstruction.Materials and Methods:Cases of oral malignancies, undergoing surgery for the same in Sri Aurobindo Medical College and PG Institute, Indore from the period from October 1, 2012, to March 31, 2015.Results:Out of analysis of 111 cases of oral malignancy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…This is likely reflected in Table 4 with larger proportions of soft tissue free flaps used for more advanced tongue tumours. This is in comparison to centres in India, where the pectoralis major myocutaneous flap remains the workhorse, with one series identifying it used for 60% of all flaps for oral cancer reconstruction [29].…”
Section: Discussionmentioning
confidence: 92%
“…This is likely reflected in Table 4 with larger proportions of soft tissue free flaps used for more advanced tongue tumours. This is in comparison to centres in India, where the pectoralis major myocutaneous flap remains the workhorse, with one series identifying it used for 60% of all flaps for oral cancer reconstruction [29].…”
Section: Discussionmentioning
confidence: 92%
“…23 Studies have suggested that history of smoking, alcohol and diabetics may contribute to the early flap related complications; however, in this study, we encountered complication of partial flap necrosis in one case that too because of poorly controlled diabetes. 24,25 Mean harvesting time for raising the flap was less than 30 minutes since it was performed as a part of neck dissection compared to the supraclavicular artery island flap (45 minutes) in oral cavity carcinoma. 26 For oral cavity defect reconstruction we recommend passing the flap pedicle through the floor of the mouth to prevent tension and shearing of the pedicle.…”
Section: Resultsmentioning
confidence: 99%
“…Patients who underwent microsurgeries were squamous cell carcinoma. Immediate reconstructive surgery is widely advised in the treatment of these patients as such treatment will increase the cure rate and reduce the morbidities and improve patient's quality of life (10,11).…”
Section: Discussionmentioning
confidence: 99%